SCIENCE EFFICIENCY IN HIGHER EDUCATION - D. Segal (Вестник Северо-Кавказского федерального университета)
For the first time, the article proposes a method for assessing the scientific effectiveness of state institutions of higher education "Science-Efficiency". Definitions of science-efficiency, innovation, product innovation, pedagogical work, research work, efficiency scientific activity etc. are given. A method for increasing the scientific effectiveness of public institutions of higher education is proposed.